Effect of storage conditions on the weight and appearance of dried blood spot samples on various cellulose-based substrates. (November 2010) - Denniff, Philip; Spooner, Neil
Background: Before shipping and storage, dried blood spot (DBS) samples must be dried in order to protect the integrity of the spots. In this article, we examine the time required to dry blood spot samples and the effects of different environmental conditions on their integrity.Results: Under ambient laboratory conditions, DBS samples on Whatman 903 ®, FTA ® and FTA ® Elute substrates are dry within 90 min of spotting. An additional 5% of moisture is lost during subsequent storage with desiccant. When exposed to elevated conditions of temperature and relative humidity, the DBS samples absorb moisture. DBS samples on FTA lose this moisture on being returned to ambient conditions. DBS samples on 903 show no visible signs of deterioration when stored at elevated conditions. However, these conditions cause the DBS to diffuse through the FTA Elute substrate.Conclusion: Blood spots are dry within 90 min of spotting. However, the substrates examined behave differently when exposed to conditions of high relative humidity and temperature, in some cases resulting in the integrity of the substrate and DBS sample being compromised. It is recommended that these factors be investigated as part of method development and validation.